STRATEGI PENGEMBANGAN MINAT DAN BUDAYA BACA PERPUSTAKAAN UMUM KABUPATEN KUBU RAYA - Santi, Santi; Madeten, Sisilya Saman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose this research is to know about the strategy that has been applied in the public library which is located around in the Archives Office and Library at Kubu Raya. This research is a descriptive research with the technique of data collection through observation, interview, and documention study. There are three people based on predetermined criteria for research participants. Some attempt was made by the library such as story telling competitions, creative wall magazines and mobile libraryas form of strategy for developing interest and reading culture for the society. Effort of empowerment was also carried out starting from the quality of service until coaching of library needs. The result obtained was the strategy for developing the interest and reading culture that has been applied to the community did not effective. Due to the service factor and also the existence of public library that has one building with the Archives Office and Library at Kubu Raya. Keywords: Strategy, Effective, Quality Library Service